Sonolysis of aqueous solutions under CO2–Ar: ESR study of variation in the number of OH radicals with CO2 concentration. (11th June 2019) - Ono, Yuki; Tanaka, Hisashi; Shinashi, Kiyoaki; Anzai, Kazunori; Harada, Hisashi
Abstract: The sono-oxidation rate of KI was accelerated in a CO2 –Ar system with low concentrations of CO2 . It was assumed that CO2 reacted with H radicals, which were produced from water together with OH radicals during sonication. Thus, a corresponding number of OH radicals are expected to remain in the reaction field. To elucidate the role of additional CO2 in the system, ESR measurements, H2 O2 production, the Fricke method and NaI dosimetry were examined. In each of these studies, improvement was confirmed upon introduction of CO2 into an Ar atmosphere, confirming the proposed mechanism.